New factory's certification process – Use of collaborative technologies as a tool - Mohiuddin, A. K. M.; Quick, Wee Hock (2004)
The technology certification process involves establishing new factory in tandem with current trend of globalization of manufacturing and shifting sites to low cost regions. The demands for accelerated learning curve and shortening start-up time require transfer of process competencies and technology. The present paper has demonstrated how collaborative technologies with the support from the fundamentals of Copy EXACTLY! (CE) methodology could be utilized to ramp-up manufacturing capacity within a shortest possible time. As a result of globalization the start-up teams that are geographically disperse are gathered to collaborate using shared critical information. It becomes more apparent and this model proves to be a forerunner in streamlining business process, reducing product time to market and developing sustainable competitive advantage.